Efficacy of Notgrass Root Extract (Cyprus rotundas L) through Inhibition Test Cell proliferation in vitro on Leukemia Cell Line HL-60 and K-562 - S.M, Agustini; E., Widjadjanto.; S., Mubarika.; M., Rifai; A.P, Dhewanty. (International Journal of Engineering and Technology, 2026)
This current research aimed at investigating the effect of natural drug (Nut grass root extract) as anti-leukemia candidate for the purpose of contributing to applied science of green technology. Background: Leukemia constitutes a hematological malignancy, positioned as the 8th highest out of top 10 malignancies across Indonesia. The cell of which is characterized to have an aggressive trait with the instance of uncontrolled proliferation. Its prevalence trends tend to increase. It is worsened by the unawareness of patients, leading to late diagnosis and unsuccessful treatment. Consequently, its morbidity and mortality increase considerably. Nut grass root extract (Cyperus rotundus L.) is projected to be a potential natural drug treated as an anti-leukemia candidate by its in vitro inhibition proliferation activity in HL-60 and K-562 leukemia cell lines. Method and sample: This current research was conducted by means of in vitro experimental method by making use of Nut grass extract tested on leukemia cell line HL-60 and K-562 for anti-proliferative inhibition effects. Results: The Nut grass root extract (Cyperus rotundus) has shown the inhibition proliferation of HL-60 and K-562 cell line, at 20ug / ml, 40ug / ml and 80ug / ml, significantly. By employing Oneway ANOVA test, it has resulted the followings: the Sig 0.000 in HL-60 and 0.000 at K-562, <p (0.01), (sig = 0.000 <0.01, R2 = 0.84) and K-562 (sig = 0.000 <0.01, R2 = 0.91). Conclusion: Alluding to the results of this research, Nut grass root extract (Cyperus rotundus L.) potentially inhibits the proliferation of HL-60 and K-562 cell lines. The increase in its intake dose is shown to be inversely proportional to the amount of proliferation. It is proven that the effective dose of Nut grass extract is 80 ug/ml. Further implication of this research is proposing Nut grass extract as the candidate for therapy in leukemia. By that, it contributes the biodiversity of natural product of Indonesia, as well as prevents and controls NCD.